Transcriptome-wide association analysis of brain structures yields insights into pleiotropy with complex neuropsychiatric traits - Bingxin Zhao (Nature Portfolio, 2021)
Brain structural traits are highly heritable and have been linked to disease. Here the authors have used gene expression data to perform a transcriptome-wide association study on 211 brain structural traits, discovering 273 associated genes.